1-Butanol dehydration in microchannel reactor: Kinetics and reactor modeling. (1st December 2015) - Khan, Yaseen; Marin, Minna; Karinen, Reetta; Lehtonen, Juha; Kanervo, Jaana
Abstract: A structured microchannel reactor (MCR) coated with pure γ -Al2 O3 was applied to investigate 1-butanol dehydration under atmospheric and isothermal conditions. Kinetic experiments were carried out and the advantages related to mass transfer properties with the application of MCR were explored under different reaction parameters and conditions. It was revealed that with the average coating thickness of 25 μ m, the operation was free of diffusional limitations and hence intrinsic kinetics could be determined by describing the reactor as pseudohomogeneous PFR with reaction kinetic expressions incorporated. Experimental data was regressed using power-law kinetics with a simplified reaction scheme for 1-butanol dehydration to butenes and dibutylether as well as with mechanistic model involving surface butoxies as relevant species. Both models were able to describe the experimental observations and the estimated values for kinetic parameters were in physically meaningful order of magnitude. A dynamic mathematical model was developed including diffusional mass transport of components and reaction inside coating, whereas, in free channel, plug flow mass transport was considered. The proposed model besides reproducing the experimental results was also able to predict presence of diffusional limitations when coating thickness is increased beyond 40 μ m . Furthermore, the simulation results show that for specific operation regimes Microchannel Reactor (MCR) outperforms packed-bed reactor, as mass transfer limitations can be appreciably reduced for 1-butanol dehydration. Abstract : Graphical abstract: Abstract : Highlights: Microreactor was applied successfully for alumina catalyzed 1-butanol dehydration. Power-law and surface reaction mechanism type kinetic models were developed. 2D models were developed to solve mass transport and reactions in microreactor. Modeling confirmed avoiding mass transport limitations in applied coating properties.